2013
DOI: 10.1051/0004-6361/201321284
|View full text |Cite
|
Sign up to set email alerts
|

The unusual afterglow of the gamma-ray burst 100621A

Abstract: Aims. With the afterglow of GRB 100621A being the brightest detected so far in X-rays, and superb GROND coverage in the optical/near-infrared during the first few hours, an observational verification of basic fireball predictions seemed possible. Methods. In order to constrain the broad-band spectral energy distribution of the afterglow of GRB 100621A, dedicated observations were performed in the optical/near-infrared with the 7-channel Gamma-Ray Burst Optical and Near-infrared Detector (GROND) at the 2.2 m MP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 52 publications
7
52
0
Order By: Relevance
“…3.4, we find the best-fit optical rise between 20 ks and 100 ks after the GRB trigger to be α reb ∼ −2.9. This high value is less extreme than α reb ∼ −8.2 and α reb ∼ −14 measured for GRB 081029 (Nardini et al 2011) and GRB 100621A (Nardini et al 2012;Greiner et al 2013), respectively, and agrees with both the typical values for FROAs reported (PV08) and with the late-bump rise steepnesses derived by Liang et al (2013) in their sample. Liang et al (2013) also found a good correlation between the optical luminosity at the rebrightening peak and the host frame peak time.…”
Section: Late Rebrighteningsupporting
confidence: 87%
See 4 more Smart Citations
“…3.4, we find the best-fit optical rise between 20 ks and 100 ks after the GRB trigger to be α reb ∼ −2.9. This high value is less extreme than α reb ∼ −8.2 and α reb ∼ −14 measured for GRB 081029 (Nardini et al 2011) and GRB 100621A (Nardini et al 2012;Greiner et al 2013), respectively, and agrees with both the typical values for FROAs reported (PV08) and with the late-bump rise steepnesses derived by Liang et al (2013) in their sample. Liang et al (2013) also found a good correlation between the optical luminosity at the rebrightening peak and the host frame peak time.…”
Section: Late Rebrighteningsupporting
confidence: 87%
“…Moreover, thanks to the rich coverage and the small uncertainties in the v, and u bands at ∼60 ks, we can identify the smaller-scale fluctuations around the rebrightening peak. Those wiggles are similar to the ones observed around the peak of the prominent optical rebrightenings of GRB 081029 and GRB 100621A discussed in Nardini et al (2011) and Greiner et al (2013), respectively. The late fading in the UVOT bands tracks the power-law decay observed in the bluer GROND bands well.…”
Section: Uvot Light Curvesupporting
confidence: 81%
See 3 more Smart Citations